(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2020)
Objective: Verify the mourning and paternal suffering in the context of perinatal death, through interviews with the mothers that suffered a gestational loss. Methods: This study has a qualitative, longitudinal, and prospective research realized through two semi-structured interviews with parents who lost children with less than 22 weeks of gestation at the high-risk maternity ward at a public hospital, in Belo Horizonte, Brazil, from February-October 2019. In the interviews, a vital trait was paternal suffering, as evidenced by the mother’s speech. This matter brought the authors attention. Results: The interviews in this study show evidence that men need to be tended regarding the time of neonatal loss. The women’s interviews expressed the suffering of their companions and demonstrated how they wished to share their pain with them during their period of mourning. The mothers provide evidence that they feel the need of their partners during gestational loss. Conclusions: Paternal suffering following neonatal loss is often ignored and forgotten about. Further research and directives of support, including supporting neonatal loss as part of the healthcare system, and meaningful steps to ensure quality treatment, are essential for making progress in this overlooked area.